Benchmarking the Computational Costs and Quality of Vibrational Spectra from Ab Initio Simulations. Issue 1 (20th November 2021) - Taherivardanjani, Shima; Elfgen, Roman; Reckien, Werner; Suarez, Estela; Perlt, Eva; Kirchner, Barbara
Abstract: The scaling behavior of ab initio molecular dynamics simulations for the different size bulk systems of liquid methanol is presented and thereby the characteristics of every system performing on either a local compute cluster or a supercomputer are analyzed. Additionally, the influence of different parameters on the quality of the infrared and Raman spectra is investigated using different simulation frameworks, including time step, convergence criteria, density functional approximation, and basis set. Both the maximally localized Wannier functions and the radical Voronoi tessellation approaches are employed to evaluate vibrational spectra from the trajectories. The results of infrared and Raman spectra are classified in two frequency regions, 500 to 1600 cm −1 and 2500 to 4000 cm −1, in order to compare and discuss the experimental spectra and the results derived from ab initio molecular dynamics simulations comprehensively. The outcome of this study guides future experimental and theoretical researchers in order to acquire a profound perception into vibrational spectra, which evolves the way of elucidating molecular structure. Abstract : The impact of different simulation parameters on the necessary computational resources and the quality of the resulting vibrational spectra are studied as well as the scaling behavior on different hardware setups. Consequently, a recommended computational setup for the calculation of infrared and Raman spectra from ab initio molecular dynamics simulations is presented.